Spirituality in Knowledge Management: Systematic Literature Review and Future Studies Suggestions - Rocha, Raysa (2020)
Knowledge Management has established itself as key to the competitive advantage of companies in the 21st century. As the mere accumulation of knowledge is insufficient, there is a corresponding need to control and supervise interactions across the organization so as to create organisational value. Thus, understanding how the composition of the main knowledge management constructs and what influences them is especially important. Sharing knowledge, a continuous process and key to creating value, has mutual trust as one of its antecedents. We here consider trust as the amount that a person is willing to impute good intentions and believe in the discourses and actions of others (Cook and Wall, 1980). This research seeks to understand whether spirituality amounts to a factor influencing the confidence and trust necessary for the sharing of organisational knowledge. Studies indeed defend spirituality as a factor promoting trust, feelings of mutuality as well as a factor generating control over negative impulses, for internal improvement, unity and interconnections among organisational members (Pawar, 2017; Tejeda, 2015; Duchon & Plowman, 2005; Mitroff & Denton, 1999). This relationship is both relevant and worthy of deeper exploration as both knowledge management and spirituality are fundamental to creating organisational value. We opted to undertake a systematic review of the literature in order to understand just which links among the constructs feature in the literature. Therefore, we made automatic searches on Web of Knowledge and EBSCO databases. Our results suggest that spirituality positively influences knowledge sharing, because it is a relevant factor itself, either in the actual sharing or indirectly through its influence over knowledge creation. However, we would emphasise that there are almost no articles interlinking these two constructs and hence the need to deepen research into this factor and improve our understanding of its influence in organisations and therefore also propose the application of different methodologies to advance studies on this subject.